Biological and psychosocial factors influence on psychical issues of perimenopause - Sobczuk, Anna; Pertyński, Tomasz; Stetkiewicz, Tomasz; Szymczak, Wiesław (Menopause Review/Przegląd Menopauzalny, 2003)
The aim of this study is answering the question if psychic functions changes are determined by biological factors or psychosocial factors. 1 104 women – patients of Menopausal Diseases Outpatient Clinic in Polish Mother’s Memorial Hospital – Research Institute were included into study. We observed that psychic well-being in perimenopausal women is more determined by stress than by hormones levels. It is proof that psychosocial factors have stronger influence on psychic functions changes in perimenopause period than biological factors. Estrogens levels influence only on some issues of well-being including general mood. This influence is complex and requires further statystical analysis.